2021
DOI: 10.21153/thl2021volno0art1314
|View full text |Cite
|
Sign up to set email alerts
|

Opening Doors in the Democratic People’s Republic of Korea

Abstract: This paper considers the opportunities for effective humanitarian collaboration in the Democratic People’s Republic of Korea (DPRK). It brings together perspectives from three individuals with extensive lived experience working in the DPRK. Collectively, these authors have worked in various sectors of international humanitarian aid and other areas of engagement such as emergency response and preparedness, education, social enterprise and tourism. The paper draws from these experiences to present lessons on ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The results of a PIAAC survey administrated by OECD revealed differences in adults’ problem–solving levels in a TRE (OECD, 2013, 2019). The OECD report indicated that the amount of access to advanced technologies is a basic component that advances digital equity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of a PIAAC survey administrated by OECD revealed differences in adults’ problem–solving levels in a TRE (OECD, 2013, 2019). The OECD report indicated that the amount of access to advanced technologies is a basic component that advances digital equity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Work–related and life–related factors also affected problem–solving skills in a digital environment. Reder (2015) investigated the digital inequity in the United States in terms of digital access, digital readiness, and digital literacy using the 2012 PIAAC data (OECD, 2013). He analyzed the responses of 5010 US participants to identify digital inequity–based ethnicity, gender, national origin, and education level and found that the overall research findings were consistent with previous research about digital inequity: younger age, higher education level, and current employment were predictors of a higher level of digital literacy.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations